EPIDEMIOLOGI PENYAKIT LAYU BAKTERI DAN PERKEMBANGAN KOMPLEKS SPESIES Ralstonia solanacearum - Setiawan, Andree Wijaya (Journal Galung Tropika, 2019)
Bacterial wilt is one of the most important diseases due to the difficulty of its control and its effect on the production of many economically valuable plants throughout the world. Ralstonia solanacearum bacteria which later will be better known as Ralstonia solanacearum species complex has a very wide range of host plants. More than 400 species of plants from 50 botanical families, including important plants that are cultivated in Indonesia such as potatoes, tomatoes, eggplants, tobacco, cloves and bananas. This review discusses the epidemiology of diseases caused by R. solanacearum, development of R. solanacearum species complex and mechanisms of action in disease management based on chemical, biological, cultivation and physical methods.